Pendampingan Pekerjaan Semenisasi Jalan Lingkungan di Desa Pulau Gadang XIII Koto Kampar - Putra, Agus Alisa; Islah, Muhammad; Puspita, Bella (Journal of Social and Community Service, 2025)
The damaged condition of neighborhood roads can hamper community activities and reduce the comfort and safety of road users. The neighborhood road in Hamlet II, Pulau Gadang Village, serves as an important access to the Mahligai Quran Tahfidz House and is the main route for community activities, but it is damaged and slippery, especially on downhill sections. This community service activity aims to provide technical assistance to the community in the cementing work of neighborhood roads to ensure construction quality meets standards and the road's service life is extended. The implementation method includes counseling, discussions, and direct field assistance related to concrete material mixing techniques (cement, sand, gravel, and water) in the correct ratio, spreading techniques, and post-work maintenance. The results of the activity show an increase in community understanding and skills in making quality concrete mixes, as well as a shared commitment to maintaining the roads that have been built. This program is expected to serve as an example for other villages in optimizing infrastructure development